Reddish Diarrhoea Caused by Excessive Ingestion of Watermelon: Mimicker of Bacterial Colitis - Taniguchi, Kazuto; Nonaka, Toshihiro; Uemichi, Kazuyasu (Journal of Nepal Paediatric Society, 2021)
Bloody diarrhoea in children is indicative of serious diseases. Although bloody diarrhoea following bacterial colitis is well known, reddish diarrhoea caused by excessive ingestion of watermelon is unknown. A two year old girl who excessively ingested watermelon presented with repeated reddish diarrhoea. A kit for fecal occult blood testing revealed that the reddish diarrhoea did not contain blood. Reddish diarrhoea caused by excessive ingestion of watermelon can be a mimicker of bacterial colitis. The kit for fecal occult blood testing was useful for differential diagnosis. We should be aware that this pitfall can be hidden in daily nutrition.